MORPHOLOGIC AND MOLECULAR FEATURES OF PRIMARY GLIOBLASTOMA IN PATIENTS SURVIVING MORE THAN 3 YEARS - M. V. Matsko; D. E. Matsko; N. M. Volkov; A. Yu. Ulitin; V. M. Moiseenko; E. N. Imyanitov; A. G. Iyevleva (Сибирский онкологический журнал, 2019)
Primary glioblastoma (GB) is a rapidly progressing central nervous system tumor with aggressive biological behavior. Long-term glioblastoma survival, defined as survival beyond 3 years, is a rare phenomenon. Various factors contributing to such prolonged lifespan have been proposed.Aim. This study aimed to compare demographic, clinical, morphologic, immunohistochemical and molecular features of primary GB in patients with different survival.Material andMethods. This prospective study included 69 patients, who were treated at A.L. Polenov Neurosurgery institute. The analysis considered clinical, morphologic, immunohistochemical (Ki67, P53, INA , EGFR) and genetic (MGMT, VEGF and PDGFRA gene expression; ID H1/2 mutational status, 1p/19q co-deletion) characteristics of the disease.Results. 11 (15.9 %) patients survived beyond 3 years. Prolonged survival was associated with younger patient age (p=0.002), use of more than 6 cycles of temozolomide in the 1st line therapy (p=0.016), use of the 2nd line therapy (p=0.017) and low level of MGMT expression in the tumor tissue (p=0.038). Other factors including patients’ gender, VEGF and PDGFRA mRNA expression levels, ID H1 mutation, 1p/19q deletion, and the immunohistochemical markers Ki67, p53, INA , EGFR, were not associated with prolonged survival (p>0.05).Conclusion. Prolonged survival in GB patients is a non-random event and can be explained by several clinical and biological factors. A high percentage of 3-year survival of GB patients in our study may be explained by an individual approach to treatment and intensive chemotherapeutic tactics (from 6 to 15 cycles of temozolomide in the 1st line therapy and use of the 2nd line therapy), as opposed to standard short treatment protocols.